Phenotypic and Genotypic Analysis of Hereditary Ataxia Patients in Sakarya City, Turkey - Sayan, Saadet (Noro Psikiyatr Ars, 2018)
INTRODUCTION: Hereditary ataxias are a group of heterogeneous diseases in regard to their clinical and genetic characteristics. Ataxia that progresses slowly may be accompanied by pyramidal and extrapyramidal findings, articulation disorders, ophthalmic movement disorders, neuropathic complaints, cognitive and behavioral abnormalies, and epilepsy. Definitive diagnosis in hereditary ataxias is based on molecular assays. History, clinical examination, laboratory and neuroimaging assist diagnosis. In our study, thirty-seven patients of suspected hereditary ataxia were examined with their clinical and genetic aspects, and the results compared with literature. METHOD: Our study included 37 patients in 22 families who presented to our center between 2010–2016, and whose familial history and phenotypic features indicated hereditary ataxia. The patients were studied for clinical findings, family tree, neuroimaging, and laboratory findings. Advanced genetic investigations were performed on peripheral venous blood samples for hereditary ataxia. RESULTS: Of the 37 patients included in our study, 21 were females and 16 were males. Genetic analyses resulted in spinocerebellar ataxia (SCA) in four families (10 patients), Friedrich ataxia (FA) in three families (eight patients), and recessive ataxia due to point mutation in one family (two patients). SCA subtyping revealed SCA 1, 2, 6 and 8 in our patients. The remaining 16 patients included in our study could not be solved so far and are under investigation. CONCLUSION: Hereditary ataxias are rare neurodegenerative disorders. Large genetic pool, ethnic and local differences complicate diagnosing even further. Our study contributes to the literature by reflecting phenotypic and genotypic characteristics of hereditary SCA patients in our region and reporting rare hereditary ataxia genotypes.